PEMERIKSAAN KESEHATAN KOLESTEROL, ASAM URAT DAN GULA DARAH DI DESA JATI, TAROGONG KALER, GARUT - Parihah Nurasiah, Sofa; Fadly Rabby, Abdi; Lery Samudra, Alif; Aristianto, Deni; Reza Firdaus, Muhammad; Citra Aulia Putri, Nurfadillah; Isyabillah Baramahdi, Nurul; Rahmawati, Rinda; Aprilia Azhari, Syifa; Barlan Aini, Wardah; Yeni Sabitha, Zakiyah (Pusat Penelitian dan Pengabdian pada Masyarakat (P3M), 2024)
Indonesia has a big challenge to face currently, namely health problems. Three important health problems include the increase in non-communicable diseases (NCDs), infectious diseases, and the emergence of diseases that should have been successfully overcome. The increase in non-communicable diseases (NCDs) will significantly increase the burden on society and the government, because handling them requires a lot of time, large costs and high technology. For this reason, it is necessary to check cholesterol, uric acid and blood glucose levels so that they can be detected early and provide education about the importance of a healthy lifestyle and prevention of diabetes mellitus, hyperlipidemia and gout. The level of public health can be improved, including by conducting health examination activities which make it possible to carry out direct health examinations, namely cholesterol, uric acid and glucose examinations.